Effects of Corporate Governance Characteristics on Audit Report Lags - Ahmed, Mohammed Ishaq; Che-Ahmad, Ayoib (International Journal of Economics and Financial Issues, 2016)
The paper examines the effects of Corporate Governance Characteristics on audit report lag (ARL) of listed banks in Nigeria. Fourteen banks were used in the study. The study covers a five year period from 2008 to 2012. Findings of the study based on robust OLS model indicate that audit quality represented by the Big 4 firms has a significant impact on ARL. Board meetings, board size, total assets and board gender have significant positive associations with ARL. However, the study did not find a significant relationship between board expertise, risk committee size and audit committee size on ARL. Generally, shareholders should maintain the use of big 4 so that report is presented at the right time to enhance confidence of the stakeholders as well as regulators. The current study dwelled on few corporate governance characteristics of the listed banks. Other potentials variables such as Company complexity, ethnicity, leverage and IFRS complexity is not included and beyond the scope of this study. Their inclusions could have given clearer picture of the determinants of Audit Report Lag in Nigerian listed banks. Keywords: Corporate governance, characteristics, audit report lags JEL Classifications: G3, M42